Role of MSK1 in the Induction of NF-κB by the Chemokine CX3CL1 in Microglial Cells - Galán-Ganga, Marcos; García-Yagüe, Ángel J.; Lastres-Becker, Isabel (Cellular and molecular neurobiology, 2019)
Microglial cells are essential mediators of neuroinflammatory processes involved in several pathologies. Moreover, the chemokine fractalkine (CX3CL1) is essential in the crosstalk between neurons and microglia. However, the exact roles of CX3CL1, CX3CL1 receptor (CX3CR1) and microglia signalling are not fully understood in neuroinflammation. In addition, the findings reported on this subject are controversial. In this work, we investigated whether CX3CL1 induced pro-inflammatory signalling activation through NF-κB pathway. We were able to show that CX3CL1 activates the pro-inflammatory pathway mediated by the transcription factor NF-κB as an early response in microglial cells. On the other side, CX3CR1-deficient microglia showed impaired NF-κB axis. Phospho-kinase assay proteome profiles indicated that CX3CL1 induced several kinases such as MAPK’s (ERK and JNK), SRC-family tyrosine kinases (YES, FGR, LCK and LYN) and most interesting and also related to NF-κB, the mitogen- and stress-activated kinase-1 (MSK1). Knockdown of MSK1 with short interfering RNAs decreased partially MSK1 protein levels (about 50%), enough to decrease the mRNA levels of Il-1β, Tnf-α and iNos triggered by stimulation with CX3CL1. These results indicate the relevance of CX3CL1 in the activation of the pro-inflammatory NF-κB signalling pathway through MSK1 in microglial cells.